Simulating fog computing in OMNeT++ - Noor Razaq Obaied Al-Rubaie; Rafal Nader Neamah Kamel; Raghda M. Alshemari (Institute of Advanced Engineering and Science, 2023)
Fog computing is a technology architecture in which data from IoT devices is received in real time by a number of nodes. These nodes process the data they receive in real time, with millisecond reaction times. The nodes communicate analytical summary data to the cloud on a regular basis. Fog computing scenario demands higher output, reduced latency, and greater performance as demand and requirements for improving performance in IoT applications grow. The resources allocation in effective manner in the fog environment is also a major problem in IoT-fog computing. Fog computing has been considered as a necessity within several IoT resources domains. In this paper the proposed fog simulation environment is focused on IoT sensors, fog node, and cloud as the used network architecture. However, the network features are properly explored in the proposed system and they are evaluated based on the throughput, latency, and channel allocation.